Bioenergy technologies, uses, market and future trends with Austria as a case study. (January 2021) - Anca-Couce, A.; Hochenauer, C.; Scharler, R.
Abstract: The current bioenergy uses and conversion technologies as well as future trends for the production of heat, power, fuels and chemicals from biomass are reviewed. The focus is placed in Austria, which is selected due to its high bioenergy utilization, providing 18.4% of the gross energy final consumption in 2017, and its strong industrial and scientific position in the field. The most common bioenergy application in Austria is bioheat with 170 PJ in 2017 mainly obtained from woody biomass combustion, followed by biofuels with 21 PJ and bioelectricity with 17 PJ. Bioheat has a stable market, where Austrian manufacturers of boilers and stoves have a strong position exporting most of their production. Future developments in bioheat production should go in the line of further reducing emissions, increasing feedstock flexibility and coupling with other renewables. For bioelectricity and biofuels, the current framework does not promote the growth of the current main technologies, i.e. combined heat and power (CHP) based on biomass combustion or biogas and first generation biofuels. However, an increase in all bioenergy uses is required to achieve the Austrian plan to be climate neutral in 2040. The current initiatives and future possibilities to achieve this increase are presented and discussed, e.g. mandatory substitution of old oil boilers, production of biomethane and early commercialization of CHP with a high efficiency or demonstration of advanced biofuels production based on gasification. Highlights: Bioenergy review focused on Austria, with a strong industrial and scientific position. Bioenergy is the main renewable and has further sustainable potential. Bioheat is the main use with a stable market but emissions must be further reduced. Shift in employed technologies for bioelectricity and biofuels production. Discussion of current outlook and future pathways for each bioenergy use.